Analisis Level Pertanyaan Siswa Berbasis Demonstrasi dalam Pembelajaran IPAS Sekolah Dasar - Maria Senisum; Yosef Firman Narut; Karmeliani Helsi Nabon (Jurnal Pendidikan dan Kebudayaan Missio, 2026)
The objective of this study is to analyze elementary school students' questions in science learning using the demonstration method. The design employed in this study is qualitative and descriptive. The research location is situated in SDI Tenda, Manggarai Regency, East Nusa Tenggara Province. The study's participants included 14 The subjects who participated in the study consisted of 143 fourth and fifth-grade students. The demonstration method was employed to facilitate science learning, with students and teachers engaging in collaborative learning activities. Furthermore, students were presented with videos containing demonstrations pertinent to the designated learning topic, specifically that of force. During the learning process, researchers obtained data by recording questions raised by students both verbally and in writing during the demonstration and by observing the video. These inquiries were subsequently analyzed to ascertain the types of inquiries that are adapted to the level of thinking in Bloom's Taxonomy. In addition to documenting students' inquiries, researchers obtained data through the conduct of interviews with classroom teachers and students. The findings of the study suggest that the inquiries posed by students during the learning process predominantly align with the cognitive domains of recollection, comprehension, and analysis. According to Bloom's Taxonomy, remembrance and comprehension are classified as lower-order thinking skills. Pedagogues must implement improvements in their instructional methodologies to facilitate the development of higher-order thinking skills in their students.